From Virtual to Reality: The Influence of Digital Engagement and Memorable Experiences on Tourist Revisit Intentions - Wang, Tz-Li; Azizurrohman, Muhammad (UI Scholars Hub, 2024)
Research Aims: This study investigates the role of Digital Engagement in mediating the relationship between Marketing Mix, Destination Image, and Revisit Intentions in the tourism industry. It also examines how Technology Adoption and Memorable Tourism Experiences moderate this relationship, providing a deeper understanding of the factors that enhance tourist loyalty in a digitally driven travel environment. Design/Methodology/Approach: A quantitative research design using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze survey data collected from international tourists who visited Taiwan. The study assessed the direct, indirect, and moderating effects of key tourism variables using reliability and validity tests, structural modeling, and mediation-moderation analysis. Research Findings: The results confirm that Marketing Mix and Destination Image positively influence Digital Engagement, which in turn has a significant impact on Revisit Intentions. Digital Engagement fully or partially mediates the effects of Marketing Mix and Destination Image, reinforcing the importance of online interactions, user-generated content, and social media engagement in shaping travel behavior. Additionally, Technology Adoption strengthens the effect of Digital Engagement on Revisit Intentions, while Memorable Tourism Experiences enhance this relationship, indicating that emotionally rich and technology-supported tourism experiences drive repeat visits. Theoretical Contribution/Originality: This study extends the Stimulus-Organism-Response (S-O-R) framework by demonstrating how Digital Engagement serves as a key psychological mechanism linking external tourism stimuli to behavioral outcomes. It also introduces Technology Adoption and Memorable Tourism Experiences as moderators, offering a more nuanced understanding of how digital interactions and personal travel experiences influence long-term destination loyalty. Practitioner/Policy Implication: The findings suggest that destination marketers and tourism policymakers should invest in interactive digital strategies, smart tourism technologies, and immersive visitor experiences to encourage repeat visits. Enhancing social media campaigns, AI-driven tourism services, and user-generated content initiatives can significantly improve Digital Engagement and long-term destination loyalty. Additionally, designing culturally enriching and emotionally memorable travel experiences can further strengthen tourists' attachment to a destination. Research Limitations/Implications: This study is limited by its cross-sectional design, which restricts the ability to track changes in tourist behavior over time. Future research should adopt a longitudinal approach to examine how Digital Engagement and Revisit Intentions evolve post-travel. Additionally, while this study focuses on Taiwan's international tourism sector, future research could explore its applicability in different cultural and regional contexts to enhance generalizability.